An overview of the genus Plesionika Bate, 1888 (Decapoda, Caridea, Pandalidae) in Asian waters - Ahamed, Ferdous; Cardoso, Irene A.; Ahmed, Zoarder F.; Hossain, Md. Y.; Ohtomi, Jun (Zootaxa, 2017)
The pandalid genus Plesionika Bate, 1888 includes 93 species and has a widespread distribution including mainly subtropical and tropical waters and some temperate waters, but most species can be found in the Indo-West Pacific. The species of this genus are benthic or nektobenthic, feeding on pelagic and benthic resources. Up to the present, the occurrence of 45 species of the genus has been reported from Asian waters. However, studies on these species from this region are mainly concerning their taxonomic report and very less their biology. Herein a key for the 45 Asian Plesionika species, and brief notes on its taxonomy are provided.